PERBANDINGAN METODE AHP DAN MAUT PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK DI MAS DARUL MUTAALIMIN TANAH MERAH KEC. GUNUNG MERIAH KAB. ACEH SINGKIL - Munte, Joni; Sinar Sinurat; Murdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The best teachers are those with profound knowledge and the ability to inspire and motivate their students. Teachers are also unsung heroes who pave the way for acquiring knowledge. Therefore, their role is crucial in educating the next generation to advance the nation. This research aims to identify the best teachers by comparing decision support system methods, specifically AHP and MAUT, to assist schools in selecting the best teachers. The study develops a system to facilitate the determination of the best teacher based on criteria set by the school. The research not only compares the two methods but also uses suitability formulas to determine the most appropriate method. With this decision support system and the methods employed, it is hoped that the MAS Darul Muta’alimin Tanah Merah will be better equipped to make decisions regarding the selection of the best teacher.